1996
DOI: 10.1089/dna.1996.15.793
|View full text |Cite
|
Sign up to set email alerts
|

A Significant Decrease of the Transcriptional Activity of p53 Mutants Deriving from Human Functional Adrenal Tumors

Abstract: Recently, our laboratory has found a high incidence (77%) of p53 gene mutations in human functional adrenal tumors. Furthermore, the majority of mutant sites were assembled at codons 100, 102, and 249. These mutation sites are not common, and there have been no studies addressing whether or not these mutants points or mutant styles cause the p53 protein to lose function. It has been well known that p53 is a transcription factor. To examine the transcriptional activities of these mutant p53 genes from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This is consistent with the report which indicated that a point mutation in codon 68 of exon 4 decreased approximately 35% transcriptional activity of the p53 gene. 28 The p53 nuclear import or retention is essential for its normal function in growth inhibition or induction of apoptosis. 23,29 A defect in the regulation of p53 nuclear import or export may result in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the report which indicated that a point mutation in codon 68 of exon 4 decreased approximately 35% transcriptional activity of the p53 gene. 28 The p53 nuclear import or retention is essential for its normal function in growth inhibition or induction of apoptosis. 23,29 A defect in the regulation of p53 nuclear import or export may result in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has been studying human functional adrenocortical tumours since 1993 (Lin et al, 1994(Lin et al, , 1996(Lin et al, , 1998a(Lin et al, ,b, 2000Shu et al, 2001;Wu et al, 2002). We have found that the K-ras gene enhanced the efficiency of cell proliferation and elevation of cortisol production in bovine adrenocortical cells.…”
mentioning
confidence: 86%
“…No electrophoretic mobility shift over the samples tested suggests normal conformations over these samples. P is the positive control of K-ras codon 12 mutant derived from SW480 human colon adenocarcinoma cell line (Lin et al, 1994;1996). As the tumorigenesis is a multigene defect (Knudson, 1989) British Journal of Cancer (1998) …”
mentioning
confidence: 99%